TEACHING FORENSIC MEDICINE TO MEDICAL STUDENTS: MODERN APPROACHES AND CHALLENGES - Haydarova Nargizaxon Axtamjon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Forensic medicine, also known as legal medicine, is a vital field that bridges the gap between medicine and law. As medical education advances, the necessity to provide students with comprehensive and practical knowledge in forensic medicine has become increasingly important. This article explores modern methodologies for teaching forensic medicine, the challenges educators face, and strategies to enhance student engagement and comprehension in this discipline.